Cooperative learning tasks in a Grade 6 intensive English as a second language class: turn-taking and degree of participation. Issue 2 (2nd April 2016) - Gagné, Nathalie; Parks, Susan
Abstract : With respect to cooperative learning, one aspect of particular interest to educators is its inclusive nature in terms of ensuring that all team members in group work are more or less equally involved in the task. Despite the inherent relevance for second language teaching, however, research is scant. To contribute to this area, the present study investigated the participation patterns of two heterogeneous groups of Grade 6 students in an intensive English as a second language (ESL) class in a Quebec school as they engaged in cooperative learning tasks. Results revealed that participation in tasks as measured by turn-taking was equally distributed amongst participants whose groups included learners of high, average and low proficiency. Results also showed that the ESL learners rarely resorted to French and thus appeared to be maximising opportunities to use the target language. Implications for classroom practice are discussed.